Natural selection mapping of the warfarin-resistance gene - Kohn, Michael H. (The National Academy of Sciences, 2000)
In theory, genes under natural selection can be revealed by unique patterns of linkage disequilibrium (LD) and polymorphism at physically linked loci. However, given the effects of recombination and mutation, the physical extent and persistence of LD patterns in natural populations is uncertain. To assess the LD signature of selection, we survey variation in 26 microsatellite loci spanning an ≈32-cM region that includes the warfarin-resistance gene (Rw) in five wild rat populations having resistance levels between 0 and 95%. We find a high frequency of heterozygote deficiency at microsatellite loci in resistant populations, and a negative association between gene diversity (H) and resistance. Contrary to previous studies, these data suggest that directional rather than overdominant selection may predominate during periods of intense anticoagulant treatment. In highly resistant populations, extensive LD was observed over a chromosome segment spanning ≈14% of rat chromosome 1. In contrast, LD in a moderately resistant population was more localized and, in conjunction with likelihood ratios, allowed assignment of Rw to a 2.2-cM interval. Within this genomic window, a diagnostic marker, D1Rat219, assigned 91% of rats to the correct resistance category. These results further demonstrate that “natural selection mapping” in field populations can detect and map major fitness-related genes, and question overdominance as the predominant mode of selection in anticoagulant-resistant rat populations.